Creating Web Pages in Secondary School Geography Classes – a Project: Planning, Realization and Evaluation (Part II) - Szymkowiak, André (Journal of Geography Education, 2003)
Information Technology in schools is an issue which has been discussed for nearly 20 years. A variety of theoretical concepts has been developed so far, most authors, however, describe successful case studies. The project described in this article is based on the theories of educational sciences and was done by 7th formers. Accordingly, the project was planned with regard to everyday life at school: the subject is taught in two lessons per week and the project is not done in a project week or workshop. The issue is discussed from the point of view of practice and didactics. Lesson planning is oriented towards the structural levels of didactics and thus bears both a legitimate and a pragmatic level. Afterwards realization and evaluation of the project are discussed.